Spatio-temporal analysis and impact assessment of trawl bycatch of Karnataka to suggest operation based fishery management options - A.P., Dineshbabu; Thomas, Sujitha; Radhakrishnan, E.V (Indian Journal of Fisheries, 2012)
The term â€˜trawl by-catchâ€™ is losing significance from commercial view point, since every fish landed is in demand. However, from the resource conservation and fishery sustainability point of view, the magnitude of resource damage caused by trawl bycatch is alarming. At Mangalore Fisheries Harbour, it was estimated that, in 2008-2009, single day operating trawlers (SDT) landed 3,515 t of fishes, out of which only 2,246 t (64%) were landed for edible purpose and the rest was rated as low value bycatch (LVB) used for miscellaneous purposes. Multiday trawlers (MDT) landed an estimated 2,20,678 t of fishes of which 1,83,145 t was retained for commercial purpose and 37,533 t (17%) was discarded. Of the retained fish, 1,67,810 t were marketed for edible use and 15,335 t (7% of the catch and 9% of the landings) was marketed as â€œlow value bycatchâ€ (LVB) mainly for fish meal production. Low value bycatch landed in Mangalore increased from 3% in 2008 to 17% in 2009, but the discards showed a reduction from 23 to 18%. From the discarded catch, 116 species of finfishes, 31 species of gastropods, 4 species of bivalves, 7 species of cephalopods, 13 species of shrimps, 3 species of stomatopods, 21 species of crabs, 3 species of lobsters and juveniles of unidentified sharks and rays were recorded. Juveniles of commercially important species formed 34% of the trawl discards by weight (44% by number). An estimated 2,733 t (464 million in number) of Platycephalus juveniles and 1341 t (333 million in number) of Nemipterus randalli were discarded by MDT operated from Mangalore during 2008-2009. Spatio-temporal analysis of bycatch data from fishing grounds off Karnataka revealed that the grounds trawled during the month of August 2009 had high discard rate in terms of quantity discarded (biomass loss) and operations during March 2008 had the highest loss of biota (biodiversity loss) in terms of number of species. The paper advocates bycatch management through effort reduction in areas and during months of high dominance of bycatch.